(untitled) - Bakhritdinov, Sh.S.; Ortikov, B.B.; Yusufov, N.I.; Ismailova, M.Sh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The purpose of the study. Hygienic assessment of the actual content of vitamin C in the daily diet of the population. Materials and methods study. Analytical and questionnaire method. A total of over 50 questionnaires were processed. The study was conducted Yangiyul district of Tashkent region. area. The results of the study. The study of the actual content in the daily diet of vitamin C showed that its amount is 60 mg, but when cooked, 50% of vitamin C will decompose. Findings. In the daily diet, the amount of vitamin C does not correspond to hygienic norms. The data obtained allowed the development of activities including the fortification of children’s nutrition in organized groups and the conduct of systematic sanitary educational work among the population